C2 IgM Natural Antibody Enhances Inflammation and Its Use in the Recombinant Single Chain Antibody-Fused Complement Inhibitor C2-Crry to Target Therapeutics to Joints Attenuates Arthritis in Mice - Banda, Nirmal K.; Tomlinson, Stephen; Scheinman, Robert I.; Ho, Nhu; Ramirez, Joseline Ramos; Mehta, Gaurav; Wang, Guankui; Vu, Vivian Pham; Simberg, Dmitri; Kulik, Liudmila; Holers, V. Michael (Frontiers in Immunology, 2020)
Natural IgM antibodies (NAbs) have been shown to recognize injury-associated neoepitopes and to initiate pathogenic complement activation. The NAb termed C2 binds to a subset of phospholipids displayed on injured cells, and its role(s) in arthritis, as well as the potential therapeutic benefit of a C2 NAb-derived ScFv-containing protein fused to a complement inhibitor, Crry, on joint inflammation are unknown. Our first objective was to functionally test mAb C2 binding to apoptotic cells from the joint and also evaluate its inflammation enhancing capacity in collagen antibody-induced arthritis (CAIA). The second objective was to generate and test the complement inhibitory capacity of C2-Crry fusion protein in the collagen-induced arthritis (CIA) model. The third objective was to demonstrate in vivo targeting of C2-Crry to damaged joints in mice with arthritis. The effect of C2-NAb on CAIA in C57BL/6 mice was examined by inducing a suboptimal disease. The inhibitory effect of C2-Crry in DBA/1J mice with CIA was determined by injecting 2x per week with a single dose of 0.250 mg/mouse. Clinical disease activity (CDA) was examined, and knee joints were fixed for analysis of histopathology, C3 deposition, and macrophage infiltration. In mice with suboptimal CAIA, at day 10 there was a significant (p <0.017) 74% increase in the CDA in mice treated with C2 NAb, compared to mice treated with F632 control NAb. In mice with CIA, at day 35 there was a significant 39% (p < 0.042) decrease in the CDA in mice treated with C2-Crry. Total scores for histopathology were also 50% decreased (p < 0.0005) in CIA mice treated with C2-Crry. C3 deposition was significantly decreased in the synovium (44%) (p < 0.026) and on the surface of cartilage (42%) (p < 0.008) in mice treated with C2-Crry compared with PBS treated CIA mice. Furthermore, C2-Crry specifically bound to apoptotic fibroblast-like synoviocytes in vitro, and also localized in the knee joints of arthritic mice as analyzed by in vivo imaging. In summary, NAb C2 enhanced arthritis-related injury, and targeted delivery of C2-Crry to inflamed joints demonstrated disease modifying activity in a mouse model of human inflammatory arthritis.